STUDENTS’ PERCEPTION TOWARD THE EFFECTIVENESS OF TEACHING ENGLISH AT UNIVERSITAS TEUKU UMAR - Endah Anisa Rahma; Rusma Setiyana (Englisia: Journal of Language, Education, and Humanities, 2019)
This paper aims to investigate the students’ perception about the effectiveness of teaching English at Universitas Teuku Umar from non-English major students. Data were collected from the students of six faculties: Economics, Social and Political Science, Fisheries and Marine Science, Engineering, and Agriculture. A number of 120 participants were selected from each faculty by using the random sampling technique. The instruments used included questionnaire and interview guide. The data were analyzed qualitatively following four effective learning criteria; material, learning method, learning motivation, and classroom management. The results showed that (1) some students were still disstatisfied with the materials given since they were hard, (2) the teaching methods used did not stimulate the students to learn English well, (3) some students did not like learning English because they could not speak like native speakers, and (4) the lecturers paid little attention towards the students’ questions and rarely did they give rewards to their students such as praising for students’ achievement. Further, the students’ obstacles in learning English included lack of vocabulary, problem in pronunciation, and grammar difficulty.